Germline and somaticNF1gene mutations in plexiform neurofibromas - Meena Upadhyaya; Gill Spurlock; Bisma Monem; Nick Thomas; Reinhard E. Friedrich; Lan Kluwe; Victor Mautner (2008)
Neurofibromatosis type 1 (NF1), a common autosomal dominant neurogenetic disorder affecting 1 in 4000 individuals worldwide, results from functional inactivation of the 17q11.2-located NF1 gene. Plexiform neurofibroma (PNF) is a congenital benign tumour present in 30-50% of NF1 patients, which in about 10-15% of cases, can develop into a malignant peripheral nerve sheath tumour (MPNST). This study aimed to characterise the NF1 germline and somatic mutations associated with such tumours by DNA analysis in 51 PNFs resected from 44 unrelated NF1 patients. Germline mutations were identified in 35 patients, of which 21 were novel. Somatic NF1 mutations were found in 29 PNF DNAs, which included 9 point mutations, 5 being novel, and 20 tumour DNA samples exhibiting, either loss of heterozygosity (LOH) of the NF1 gene region (16 tumours), or complete or partial NF1 gene deletions analyzed by multiplex ligation-dependent probe amplification (MPLA) analysis. The type of NF1 germline mutations detected in patients with PNF were similar to those detected in most NF1 patients. LOH of the NF1 gene region, as identified by marker analysis and/or MLPA, was detected in only 20/29 (69%) PNFs, compared to the >90% LOH previously found in MPNST. This systematic analysis of the NF1 germline and somatic mutations associated with PNF development suggest that in most such tumours neither the NF1 somatic mutation type, nor its gene location, is influenced by the underlying NF1 germline mutation. Evidence for LOH involving the TP53 gene identified in the PNFs is also reported for the first time. © 2008 Wiley-Liss, Inc.